2014
DOI: 10.1088/0954-3899/42/1/015003
|View full text |Cite
|
Sign up to set email alerts
|

Limit on the pion distribution amplitude

Abstract: The pion distribution amplitude (DA) can be related to the fundamental QCD Greenʼs functions as a function of the quark self-energy and the quark-pion vertex, which in turn are associated with the pion wave function through the Bethe-Salpeter equation. Considering the extreme hard asymptotic behavior in momentum space allowed for a pseudoscalar wave function, which is limited by its normalization condition, we compute the pion DA and its second moment. From the resulting amplitude, representing the field theor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…In its simplest and original version (Donnachie-Landshoff model [45,46,47]), this trajectory is degenerate, representing both C = +1 and C = −1 mesonic trajectories, namely (a, f ) and (ρ, ω), respectively. However, several amplitude analyses, including also both spectroscopic and scattering data, have indicated that the best data reductions are obtained with non-degenerate trajectories [48,49,50,51,52]. In this case and with our previous notation [37], the low-energy contribution can be expressed as…”
Section: Analytic Parametrizations For the Total Cross-sectionmentioning
confidence: 90%
“…In its simplest and original version (Donnachie-Landshoff model [45,46,47]), this trajectory is degenerate, representing both C = +1 and C = −1 mesonic trajectories, namely (a, f ) and (ρ, ω), respectively. However, several amplitude analyses, including also both spectroscopic and scattering data, have indicated that the best data reductions are obtained with non-degenerate trajectories [48,49,50,51,52]. In this case and with our previous notation [37], the low-energy contribution can be expressed as…”
Section: Analytic Parametrizations For the Total Cross-sectionmentioning
confidence: 90%
“…Variant 2 (V2): Also initialized with the Direct Fit results. In this case, we consider γ = 2 (fixed) and b 1 and b 2 also fixed to the intercepts extracted from the spectroscopic data on the a 2 /f 2 and ρ/ω mesons trajectories, obtained by Luna, Menon and Montanha, namely b 1 = 0.452 and b 2 = 0.558 [56] (fifth column in Table I).…”
Section: Variant 1 (V1)mentioning
confidence: 99%
“…suggesting also some missing systematic uncertainty effect which, however, was never identified. As a consequence, except for some particular studies excluding one or another set [27][28][29], most analyses consider the complete dataset with the three points at 1.8 TeV. As a further curious consequence, most analyses are not compatible with none of them, since the curves lie between the CDF datum (upper) and the E710/E811 data (lower).…”
Section: Discussionmentioning
confidence: 99%